Removal of lead ions from wastewater with economical adsorbents: A preliminary finding / Megat Ahmad Kamal Megat Hanafiah, Shariff Che Ibrahim and Muhd Zu Azhan Yahya - Megat Hanafiah, Megat Ahmad Kamal; Che Ibrahim, Shariff; Yahya, Muhd Zu Azhan (2004)
The removal of lead from synthetic wastewater with economical materials particularly Hevea brasiliensis (HE) leaf. Imperata cylindrica (IC) leaf and Sterculia spp (SS) leaf was investigated by the batch mode method. The influence of pH and particle size on the removal of lead was determined. The removal percentages by adsorption onto HE, SS and IC showed high values for lead ions. The extent of lead removal increased with decrease in the size of adsorbents and increase in the pH of the solution. Lead ions were removed best (75%) by SS and IC at pH 7 by using adsorbent size of 500 µm. Highest removal of lead by HE was recorded by using the size of 500 µm, at pH 5. Due to their demonstrated ability for lead uptake and low production cost, these natural wastes are attractive adsorbents for the removal of lead from waste streams.